Outbreak and Spread of Bacterial Canker of Kiwifruit Caused by Pseudomonas syringae pv. actinidiae Biovar 3 in Korea - Kim, Gyoung Hee (Plant Pathol J, 2016)
A bacterial pathogen, Pseudomonas syringae pv. actinidiae (Psa), is a causal agent of kiwifruit bacterial canker worldwide. Psa biovar 3 (Psa3) was first detected in 2011 at an orchard in Dodeok-myeon, Goheunggun, Jeonnam Province in Korea. In this study, we present the results of an epidemiological study regarding Psa3 occurrence on kiwifruit orchards in Korea for the period of 2013 to 2015. Since the first detection of Psa3 in 2011, there was no further case reported by 2013. However, Psa3 was rapidly spreading to 33 orchards in 2014; except for three orchards in Sacheonsi, Gyeongnam Province, most cases were reported in Jeju Island. Entering 2015, bacterial canker by Psa3 became a pandemic in Korea, spreading to 72 orchards in Jeju Island, Jeonnam, and Gyeongnam Provinces. Our epidemiological study indicated that the first Psa3 incidence in 2011 might result from an introduction of Psa3 through imported seedlings from China in 2006. Apart from this, it was estimated that most Psa3 outbreaks from 2014 to 2015 were caused by pollens imported from New Zealand and China for artificial pollination. Most kiwifruit cultivars growing in Korea were infected with Psa3; yellow-fleshed cultivars (Yellow-king, Hort16A, Enza-gold, Zecy-gold, and Haegeum), red-fleshed cultivars (Hongyang and Enza-Red), green-fleshed cultivars (Hayward and Daeheung), and even a kiwiberry (Skinny-green). However, susceptibility to canker differed among cultivars; yellow- and red-fleshed cultivars showed much more severe symptoms compared to the green-fleshed cultivars of kiwifruit and a kiwiberry.